Does participation in the arts have a positive psycho-social impact for adolescents? - Jade, Hogg (2014)
Abstract Background: Adolescence is a time of great physiological, psychological and social change. This paper will be highlighting how participation in an art group can benefit adolescent psychosocial development. In order to address this, adolescents need to be considered on a psychological, social and political level. Since the 2008 financial crisis and subsequent recession, adolescents have faced limited training and employment opportunities (Prince’s Trust, 2014). Alongside this, the UK has great social inequalities, which although the government aims to tackle, are still evident (Wilkinson and Pickett, 2009). Furthermore, adolescents face going through their own personal transitions into adulthood which holds its own complexities. Art groups have proven benefits, many of which can be applicable to adolescents (Twiss and Cooper, 2000). Aims: Identify and understand the major psychological change adolescent’s experience. Also, use literature and theory to establish the main issues faced by adolescents in today’s society. Furthermore, establish the benefits of art groups for adolescents by examining the strengths and weaknesses of art groups in the literature. Conclusion: Adolescents have suffered from the impact of the economic downfall and struggle to find jobs, apprenticeships and training opportunities (The Prince’s Trust, 2014). This causes individuals to be at risk of the “vicious circle” of social exclusion which involves a multitude of issues including; social isolation, poverty and mental health problems (Marmot, 2010). Some art groups have been set up to help tackle these issues. However, there is limited number of published literature on community art groups for adolescents. Keywords: adolescent, arts in health, young people, community art group, art group, communities